Analisis Perbedaan Integritas Akademik Terkait Tanggung Jawab dan Menghormati antara Mahasiswa S-1 Profesi Bidan dan S-2 Ilmu Kebidanan di Universitas ‘Aisyiyah Yogyakarta - Embun Nadya; Wiwik Kusumawati; Enny Fitriahadi (FORIKES, 2022)
Background: academic integrity violation occurs due to low self-control, self-efficacy and academic achievement which 10% and 90% respectively influenced by the penalty level given, peer influence, perception of materials and lecturers and other factors. Purpose: to determine the difference in academic integrity regarding responsibility and respect between undergraduate midwifery profession students and postgraduate midwifery science. Methods: comparative analytical observational research with cross sectional study approach and Chi-Square data analysis. Data collection was using Sue Roof questionnaire which contained violations of academic integrity. Results: perception of responsibility and respect with a value of p 0.023, opinion of responsibility and respect with a value of p 0.040, conduct of responsibility and respect with a value of p 0.011, commitment of responsibility and respect with a value of p 0.023 and sanctions of responsibility and respect with a p value of 0.027. Conclusion: The academic integrity value of undergraduate students is lower than postgraduate students; postgraduate students are more responsible and have respect; The level of awareness, experience and level of education makes postgraduate students have good integrity while pressure and self-ability are the reason undergraduate students commit academic cheating. Recommendation: it is expected that all parties will play a role in instilling the value of academic integrity in students and institutions to impose strict sanctions on violators of academic integrity.Keywords: academic integrity; midwifery students; respect; responsibilityABSTRAK Latar belakang: kecurangan integritas akademik terjadi karenarendahnya kontrol diri, efikasi diri dan prestasi akademik yang memiliki peran 10% dan 90% dipengaruhi oleh tingkat hukuman yang diberikan, pengaruh teman sebaya, persepsi terhadap materi dan dosen dan faktor lainnya. Tujuan: untuk mengetahui perbedaan integritas akademik terkait tanggung jawab dan menghormati antara mahasiswa S-1 profesi bidan dan S-2 ilmukebidanan. Metode: penelitian observasional analitik komparatif dengan pendekatan cross sectional study dan analisis data Chi-Square. Pengumpulan data menggunakan kuisioner Sue Roof tentang pelanggaran integritas akademik. Hasil:persepsi tanggung jawab dan menghormati dengan nilai p 0,023, opini tanggung jawab dan menghormati dengan nilai p 0,040, perilaku tanggung jawab dan menghormati dengan nilai p 0,011, komitmen tanggung jawab dan hormati dengan nilai p 0,023 dan sanksi tanggung jawab dan menghormati dengan nilai p 0.027. Kesimpulan: Nilai integritas akademik S-1 lebih rendah dari S-2; Mahasiswa S-2 lebih bertanggung jawab dan memiliki rasa hormat; Faktor tingkat kesadaran, pengalaman dan tingkat pendidikan menjadikan mahasiswa S-2 memiliki integritas yang baik sedangkan tekanan dan kemampuan diri menjadi alasan mahasiswa S-1 melakukan kecurangan akademik. Saran: diharapkan semua pihak ikut berperan dalam menanamkan nilai integritas akademik pada mahasiswa dan pihak institusi memberikan sanksi yang tegas bagi pelanggar intgeritas akademik.Kata kunci: integritas akademik; tanggung jawab; menghormati; mahasiswa kebidanan